MORE4IOT - um middleware multiprotocolo para internet das coisas - Alves, Rodolfo Felipe Medeiros (2021)
The term Industry 4.0 is used to synthesize the changes promoted in industrial processes through technology. In Brazil, there are great challenges for the economy to grow in the world ranking of innovation. Despite this, the data show that the fourth industrial revolution is an opportunity for the country, mainly in agriculture, which in 2021 should reach a record in the gross value of agricultural production of 1.076 trillion reais. The Internet of Things (IoT) is one of the pillars of Industry 4.0 and can contribute, for example, to precision agriculture to improve the monitoring and control of processes involving agricultural production. The objective of IoT is to bundle the global network infrastructure with scalable resources based on communication protocols and physical objects or devices that have an identity and attributes to achieve synergy and offer innovative services. However, inserting the IoT in any environment is very costly and requires a great amount of adaptation. Therefore, this work aims to allow the construction of Internet of Things applications, which use and connect different devices with different communication protocols without significant adaptations. For this, MORE4IoT which is a multiprotocol middleware based on a microservices architecture was defined and developed to assist in the construction of IoT applications, which has two main components: an infrastructure based on microservices to assist in communication, resource management, data and control actions; and, a component that must be included in the device to assist in communication and control rules. In addition, the middleware was validated through the construction of a prototype applied to precision agriculture using the communication and management mechanisms provided by MORE4IoT. As a result, middleware simplified the construction of communication by protocols, control rules and solved the device management of the application